HAX-1 regulates SERCA2a oxidation and degradation. (January 2018) - Bidwell, Philip A.; Liu, Guan-Sheng; Nagarajan, Narayani; Lam, Chi Keung; Haghighi, Kobra; Gardner, George; Cai, Wen-Feng; Zhao, Wen; Mugge, Luke; Vafiadaki, Elizabeth; Sanoudou, Despina; Rubinstein, Jack; et al.
Abstract: Ischemia/reperfusion injury is associated with contractile dysfunction and increased cardiomyocyte death. Overexpression of the hematopoietic lineage substrate-1-associated protein X-1 (HAX-1) has been shown to protect from cellular injury but the function of endogenous HAX-1 remains obscure due to early lethality of the knockout mouse. Herein we generated a cardiac-specific and inducible HAX-1 deficient model, which uncovered an unexpected role of HAX-1 in regulation of sarco/endoplasmic reticulum Ca-ATPase (SERCA2a) in ischemia/reperfusion injury. Although ablation of HAX-1 in the adult heart elicited no morphological alterations under non-stress conditions, it diminished contractile recovery and increased infarct size upon ischemia/reperfusion injury. These detrimental effects were associated with increased loss of SERCA2a. Enhanced SERCA2a degradation was not due to alterations in calpain and calpastatin levels or calpain activity. Conversely, HAX-1 overexpression improved contractile recovery and maintained SERCA2a levels. The regulatory effects of HAX-1 on SERCA2a degradation were observed at multiple levels, including intact hearts, isolated cardiomyocytes and sarcoplasmic reticulum microsomes. Mechanistically, HAX-1 ablation elicited increased production of reactive oxygen species at the sarco/endoplasic reticulum compartment, resulting in SERCA2a oxidation and a predisposition to its proteolysis. This effect may be mediated by NAPDH oxidase 4 (NOX4), a novel binding partner of HAX-1. Accordingly, NOX inhibition with apocynin abrogated the effects of HAX-1 ablation in hearts subjected to ischemia/reperfusion injury. Taken together, our findings reveal a role of HAX-1 in the regulation of oxidative stress and SERCA2a degradation, implicating its importance in calcium homeostasis and cell survival pathways.